Comparison of an automated rapid plasma reagin (RPR) test with the conventional RPR card test in syphilis testing. Issue 12 (31st December 2014) - Lee, Jong-Han; Lim, Chae Seung; Lee, Min-Geol; Kim, Hyon-Suk
Abstract : Objective: We compared the automated non-treponemal reagin (rapid plasma reagin (RPR)) test with the conventional RPR card test for usefulness in clinical applications. Setting: A comparative study of laboratory methods using clinical specimens in a single institute. Participants: A total of 112 serum samples including 59 Treponema pallidum particle agglutination (TPPA)-positive and 53 TPPA-negative specimens were evaluated. Outcome measures: HiSens Auto RPR LTIA (HBI, Anyang, Korea) was compared with Macro-Vue RPR Card Tests (Becton Dickinson BD Microbiology Systems, Sparks, Maryland, USA). Treponemal-specific tests were performed by Serodia TPPA assay (Fujirebio, Tokyo, Japan). The percentage agreement, κ value and overall sensitivity and specificity of the two RPR tests were compared. Seroconversion rates after treatment were also compared for each RPR test. Results: The percentage agreement between the two RPR tests was 78.6% (κ 0.565; 95% CI 0.422 to 0.709). Sensitivity and specificity of the automated RPR test relative to the TPPA test was 52.5% (95% CI 39.1% to 65.7%) and 94.3% (95% CI 84.3% to 98.8%), respectively, while the same values for the conventional RPR card test were 86.4% (95% CI 75% to 93.9%) and 94.3% (95% CI 84.3% to 98.8%), respectively. The conventional RPR card test showed overall higher positivity than the automated RPR test, whereas the automated RPR test showed higher seroconversion (43.5%, 10/23) than the conventional RPR card test (4.3%, 1/23) in treated patients. Conclusions: The automated RPR test showed overall lower sensitivity than the conventional RPR test based on the treponemal test, but higher seroconversion after treatment. The automated RPR test could be used to monitor treatment response, especially in the reverse screening algorithm in syphilis testing.